2020
DOI: 10.1159/000512290
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Outcomes of a Hospital-to-Community Model of Integrated Care for Dementia

Abstract: <b><i>Introduction:</i></b> Living with dementia is challenging for persons with dementia (PWDs) and their families. Although multi-component intervention, underscored by the ethos of person-centred care, has been shown to maintain quality of life (QOL) in PWDs and caregivers, a lack of service integration can hinder effectiveness. <b><i>Methods:</i></b> CARITAS, an integrated care initiative provided through a hospital-community care partnership, endeavours to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Given previous studies describing integrated care as needing to be person-centred and the 'patient's perspective is at the heart of any discussion about integrated care' (Lloyd & Wait, 2005), exploratory studies with a focus on patient experience should be considered to develop a deeper understanding of what integrated dementia care means to those accessing services. Further, whilst quantitative studies exploring the impact of integrated dementia care interventions have shown some positive results, for example: improvements in memory; quality of life; mental health of the person living with dementia; and reduced carer 'burden' (Ha et al, 2020;Zwingmann et al, 2018), future studies using a mixed-methods approach may provide a more robust understanding of why some interventions work well and others do not.…”
Section: Discussionmentioning
confidence: 99%
“…Given previous studies describing integrated care as needing to be person-centred and the 'patient's perspective is at the heart of any discussion about integrated care' (Lloyd & Wait, 2005), exploratory studies with a focus on patient experience should be considered to develop a deeper understanding of what integrated dementia care means to those accessing services. Further, whilst quantitative studies exploring the impact of integrated dementia care interventions have shown some positive results, for example: improvements in memory; quality of life; mental health of the person living with dementia; and reduced carer 'burden' (Ha et al, 2020;Zwingmann et al, 2018), future studies using a mixed-methods approach may provide a more robust understanding of why some interventions work well and others do not.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of programmes described a focus on lowering hospital resource utilisation by supporting patients during care transitions (36%) [28,31,39,42,43,45,46,50,55,56], and facilitating referrals from the specialist outpatient clinics (SOCs) to primary care providers (PCPs) (18%) [28,39,40,51,54]. The remaining 13 articles (46%) aimed to optimise the management of specific chronic diseases [29,[31][32][33][34][35]37,45,46,49,50,52,53]. Importantly, heightened emphasis on reducing hospital resource utilisation and facilitating care transitions to lower levels of care aligns with the local vision of shifting care Beyond Hospital to Community.…”
Section: Operational Characteristics Of Programmes Reviewedmentioning
confidence: 99%
“…Congruent to shifting care Beyond Hospital to Community, most of the initiatives reviewed provide care off-site, i.e., via phone calls or at patients' homes. Half of the articles reviewed depicted off-site care delivery [30,32,36,38,[41][42][43][44]47,48,[51][52][53]55], nine in the hospital setting [29,31,39,40,45,46,49,50,54] and three in primary care settings [34,35,37]. Only Ang et al and Ha et al, reported care delivery occurring in both hospital and primary care settings under the same respective programme [28,33].…”
Section: Operational Characteristics Of Programmes Reviewedmentioning
confidence: 99%
See 2 more Smart Citations